2020
DOI: 10.1038/s41598-020-59606-y
|View full text |Cite
|
Sign up to set email alerts
|

Breast Arterial Calcification is Associated with the Progression of Coronary Atherosclerosis in Asymptomatic Women: A Preliminary Retrospective Cohort Study

Abstract: CCTA acquisition and analysis. As previously described, CCTA was performed using a 64-detector row computed tomography (CT) scanner (Brilliance 64; Philips Medical Systems, Best) and the images were transferred to an offline 3-dimensional workstation. CCTA images were independently analysed for CAC and CAP 6. The CAC score (CACS) was measured using the Agatston scoring system 8. CAP was defined as the presence of any clearly discernible atherosclerotic plaque lesion >1 mm 2 that could be discriminated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…Smoking, HT, and hyperlipidemia are known and proven risk factors for atherosclerosis (11,31,32,42). Our study determined that these chronic diseases did not significantly affect the BAC score, according to the quantitative statistical multivariate analysis.…”
Section: A B a Bmentioning
confidence: 75%
See 1 more Smart Citation
“…Smoking, HT, and hyperlipidemia are known and proven risk factors for atherosclerosis (11,31,32,42). Our study determined that these chronic diseases did not significantly affect the BAC score, according to the quantitative statistical multivariate analysis.…”
Section: A B a Bmentioning
confidence: 75%
“…It has been suggested that BAC must be reported as part of routine mammography examinations. Patients, radiologists, and referring physicians can use the information as part of collective decision-making regarding cardiac evaluation to maximize the benefit of preventive cardiology strategies (11,17,(39)(40)(41)(42). Besides, mammography is routinely used as a screening test for breast cancer.…”
Section: A B a Bmentioning
confidence: 99%
“…Prevalence of BAC on mammography Распространенность КАМЖ при маммографии Введение Кальциноз артерий молочной железы (КАМЖ), легко выявляемый при скрининговой маммографии, морфологически представляет собой кальциноз медиальной оболочки артерий, и с онкологической точки зрения рассматривается как случайная «доброкачественная» находка. Вместе с тем имеется значительный массив данных о связи КАМЖ с высокой распространенностью сердечно-сосудистых заболеваний (ССЗ) [1][2][3], риском неблагоприятных сердечно-сосудистых (СС) событий [1,3,4], кальцинозом коронарных артерий, наличием коронарных атером и высокой вероятностью их прогрессирования [5]. Высказывается мнение, что у женщин наличие КАМЖ может служить новым гендер-специфическим маркером СС риска [4,5], что открывает перспективы для использования маммографии в качестве инструмента ранней диагностики не только рака молочной железы, но и ССЗ.…”
Section: распространенность и степень тяжести кальциноза артерий моло...unclassified
“…Вместе с тем имеется значительный массив данных о связи КАМЖ с высокой распространенностью сердечно-сосудистых заболеваний (ССЗ) [1][2][3], риском неблагоприятных сердечно-сосудистых (СС) событий [1,3,4], кальцинозом коронарных артерий, наличием коронарных атером и высокой вероятностью их прогрессирования [5]. Высказывается мнение, что у женщин наличие КАМЖ может служить новым гендер-специфическим маркером СС риска [4,5], что открывает перспективы для использования маммографии в качестве инструмента ранней диагностики не только рака молочной железы, но и ССЗ.…”
Section: распространенность и степень тяжести кальциноза артерий моло...unclassified
See 1 more Smart Citation